Sale of Rights in Dispute between Sharia Law and Algerian Law - Gherbi , Soreya; Boudjani , Abdelhakim (Indonesian Journal of Social Science Research, 2024)
The sales contract is one of the most important contracts in the lives of individuals and nations, as it is the customary means of exchanging money after the decline of bartering. With the passage of time, the shortcomings of bartering became evident due to the development of industry and commerce, and the varying needs of people. This led to the emergence of the sales contract, as it became a more suitable method of transaction compared to bartering, serving as a common ground for transactions between parties more than bartering. The aim of this research is to analyze the concept of rights sale in the conflict between Algerian law and Islamic law, and to understand the differences and similarities between the two legal systems in this context. Methods Used: An analytical methodology was employed, involving a comparative study of laws and judicial rulings in Algerian law and Islamic law pertaining to rights sale. Findings: The study revealed significant differences between Algerian law and Islamic law regarding the concept, conditions, and transactions of rights sale. Additionally, the findings pointed out some of the challenges and contradictions that arise when applying Sharia principles in a non-Islamic legal system.